Melon, Casaba—Cucumis melo L. (Inodorus group) - James M. Stephens (EDIS, 2003)
This document provides an overview of the casaba melon, a member of the winter melon group related to cantaloupes and honeydews. It details the fruit’s origin, physical characteristics, varieties, and cultivation practices, particularly in Florida. Casabas are noted for their wrinkled skin, thick flesh, and mild sweetness. Due to their long maturation period and susceptibility to leaf diseases, they are not widely grown in Florida. The document also outlines recommended planting times and cultural practices to improve growth and yield. Original publication date May 1994.